Geochemistry of travertine deposits in the Eastern Anatolia District: an example of the Karakoçan-Yoğunağaç (Elazığ) and Mazgirt-Dedebağ (Tunceli) travertines, Turkey - Kalender, Leyla; Okan, Özlem Öztekin; İnceöz, Murat; Çetindağ, Bahattin; Yıldırım, Vesile (My University, 2015)
The Karakoçan-Yoğunağaç (Elazığ) and Mazgirt-Dedebağ (Tunceli) travertines, which are related to thermal springs, aresituated on the right-lateral strike-slip Karakoçan Fault Zone (KFZ) and left-lateral strike-slip Pamuklu Fault Zone (PFZ) in easternAnatolia. The surface area of the travertines varies from m2 to km2. Morphologically, the travertines are classified as ridge, banded, andterrace types due to deposition in different ways, in the releasing/restraining bends of the KFZ and PFZ and on the segments of faults.The banded travertines were dated by U-series, and an age of 160,000 ± 76 years was determined in only one sample from the Mazgirt- Dedebağ area. Travertines primarily consist of low magnesian calcite and form the spherical pisoids. Amorphous iron oxide (up to2.93%), other metal concentrations (As: 753.3 ppm; Co: 14.3 ppm; Cu: 4.9 ppm; Mn: 4094 ppm; Zn: 4.7 ppm), and heavy stabile isotopevalues (δ18Ocalcite (SMOW)and δ13Ccalcite (PDB))have increasing trends from the outside to the inside of the banded travertines. Theestimated δ18OH2O isotope values in both ancient and modern travertine samples show that the thermal water temperature decreasedapproximately 17 °C from ancient to modern travertine formations. Algal species of Cyanophyta (blue/green algae), Chlorophyceae(green algae), and Bacillariophyta are predominant in both the Mazgirt and Karakoçan travertines. Oscillatoria is dominant in thestudied thermal waters that are found as superficial mats on the travertines and are often common in sulfide-rich thermal waters.
Keywords: Jeokimya ve Jeofizik; Jeoloji; Mineraloji